2018
DOI: 10.1007/s00426-018-1109-1
|View full text |Cite
|
Sign up to set email alerts
|

No evaluative conditioning effects with briefly presented stimuli

Abstract: Evaluative conditioning (EC) changes the preference towards a formerly neutral stimulus (Conditioned Stimulus; CS), by pairing it with a valent stimulus (Unconditioned Stimulus; US), in the direction of the valence of the US. When the CS is presented suboptimally (i.e., too briefly to be consciously perceived), contingency awareness between CS and US can be ruled out. Hence, EC effects with suboptimally presented CSs would support theories claiming that contingency awareness is not necessary for EC effects to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(49 reference statements)
1
5
2
Order By: Relevance
“…The results of the present study seem to contradict the conclusions of most recent studies on subliminal instrumental and evaluative conditioning (e.g., Heycke & Stahl, 2020;Skora et al, 2021a, b), which found that conditioning does not occur when the stimuli are exposed subliminally. As explained in the introduction, a failure to find conditioning effects for unconsciously presented stimuli might mean that consciousness is necessary for learning and conditioning.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of the present study seem to contradict the conclusions of most recent studies on subliminal instrumental and evaluative conditioning (e.g., Heycke & Stahl, 2020;Skora et al, 2021a, b), which found that conditioning does not occur when the stimuli are exposed subliminally. As explained in the introduction, a failure to find conditioning effects for unconsciously presented stimuli might mean that consciousness is necessary for learning and conditioning.…”
Section: Discussioncontrasting
confidence: 99%
“…A first approach is to prevent the conscious perception of the predictive (conditioned) stimulus, during the conditioning procedure. Most recent studies that have exposed subliminally the conditioned stimuli, using improved methods for ensuring the unconscious character of exposure, have found evidence against instrumental conditioning outside of awareness (T Reber et al, 2018;Skora et al, 2021a, b; see also, e.g., Heycke & Stahl, 2020;Hogden et al, 2018 for similar results obtained in other conditioning paradigms; contrast Greenwald & De Houwer, 2017).…”
Section: Producing Unawarenessmentioning
confidence: 98%
“…Although conducted in a different paradigm, the results of the present study present a different picture compared to most recent studies on subliminal instrumental and evaluative conditioning (e.g., Heycke & Stahl, 2020;Skora et al, 2021a, b), which found that conditioning does not occur when the stimuli are exposed subliminally. The conclusion emerging from these studies point towards the necessity of consciousness for learning the appetitive value of stimuli.…”
Section: Discussioncontrasting
confidence: 98%
“…The non-significant differences across CS evaluations reported here corroborates a recent report by Heycke and Stahl (2020), who found no evidence of subliminal conditioning on CS evaluations when CS were undetected. None of the CS presented here were detected during visibility checks, and CS evaluations were similarly unaffected by conditioning 2 .…”
Section: Cs Visibilitysupporting
confidence: 91%